Erratum: Comparing the Use of Visual Analogue Scales and Likert-type Scales in International Agricultural and Extension Education Surveys - JIAEE Editors (Journal of International Agricultural and Extension Education, 2024)
Correction: The DOI of the article "Gay, K. D., Leal, A., Ruth, T. K., Lamm, A. J., & Rumble, J. N. (2015). Comparing the Use of Visual Analogue Scales and Likert-type Scales in International Agricultural and Extension Education Surveys. Journal of International Agricultural and Extension Education, 22(2), 37-51” was incorrect as published. The correct DOI is: 10.4148/2831-5960.1259